Penglibatan dan Sumbangan Harun Taib dalam Parti Islam Semalaysia (PAS) - Haji Zakaria, Mohd Khairul Amin; Abdul Rahman, Mohamad Zaidi; Mohamad, Shukeri (Online Journal of Research in Islamic Studies, 2016)
Harun Taib involvement in Pan-Malaysian Islamic Party (PAS) began as early as teens until the end of his life. Various responsibilities and the trustworthiness carried him throughout his struggle with PAS. He was starting as an amilin (worker) to PAS until the highest position as the Chairman of the Council of Ulama. Undeniably, in playing his roles especially as the Chairman of the Council of Ulama, he has contributed to the development of the Party and also to the whole community. The objective of this study is to identify the involvements and contributions of Harun Taib in PAS. This studywill be using the qualitative methodological approach comprehensively by focusing on the instrument of literature review, analysis of documents, interviews and observations. This study argues that Harun Taib plays an important role throughout his involvement in PAS by contributing in the various sectors, particularly in tarbiyyah. His contributions in tarbiyyah are so vital in producing the future leadership of PAS. Indeed, the involvements and contributions of Harun Taib in PAS are inspiring and deserving recognition and appreciation from the public.